Is There a Future for Chemoprevention of Prostate Cancer? - Bosland, Maarten C. (Cancer Prev Res (Phila), 2016)
The outcome of the Selenium and Vitamin E Cancer Prevention Trial (SELECT), demonstrating harm and no preventive activity of selenomethionine and α-tocopherol for prostate cancer, and the lack of approval by the US Food and Drug Administration for the use of 5α-reductase inhibitors to prevent prostate cancer have cast doubt about the future of chemoprevention of prostate cancer. This article attempts to critically assess whether the notion that chemoprevention of prostate cancer has no future is warranted. Risk of prostate cancer is modifiable and chemoprevention of prostate cancer, particularly fatal/lethal cancer, is both needed and possible. However, the approach to prostate cancer chemopreventive agent development has not followed a rational and systematic process. To make progress, the following steps are necessary: (1) identification of intermediate biomarkers predictive of fatal/lethal disease; (2) development of a rational approach to identification of candidate agents, including high-throughput screening and generation of information on mechanism and biology of candidate agents and potential molecular targets; and (3) systematic evaluation of the predictive value of preclinical models, Phase II trials, and intermediate biomarkers for the outcome of Phase III trials. New Phase III trials should be based on adequate preclinical and Phase II studies.